Rancang Bangun Kunci Pintu Perpustakaan Otomatis Menggunakan Algoritma Histogram of oriented gradients Berbasis Mini-PC - Muhammad Fauzan Azhim; Werman Kasoep; Desta Yolanda (CHIPSET, 2023)
Facial recognition has been a long-standing problem in computer vision. Recently, Histograms of Oriented Gradients (HOGs) have been shown to be effective descriptors for object recognition in general and face recognition in particular. In this study, HOGs are used as an algorithm to achieve facial recognition, which aims to recognize the faces of registered students when visiting the library without the need to fill in the attendance list in the visitor book and open the door and lock the door automatically.